Efficient collusion in repeated auctions with communication - Masaki Aoyagi (Osaka University, Institute of Social and Economic Research (ISER), 2002)
This paper studies collusion in repeated auctions when bidders communicate prior to each stage auction. The paper presents a folk theorem for independent and correlated private signals and general interdependent values. Specifically, it identifies conditions under which an equilibrium collusion scheme is fully efficient in the sense that the bidders' payoff is close to what they get when the object is allocated to the highest valuation bidder at the reserve price in every period.
Keywords: C72; D82; 330; collusion; auction; communication; folk theorem; Auktionstheorie; Kommunikation; Theorie; Wiederholte Spiele